THE IMPORTANCE OF SELF-STUDY SKILLS IN LEARNING ENGLISH LANGUAGE (Ta'limning zamonaviy transformatsiyasi, 2024)
Annotation: Self-study skills are incredibly important when it comes to learning the English language. While attending classes and working with a teacher is beneficial, the majority of the learning process happens outside of the classroom. Developing strong self-study skills can greatly enhance your language learning experience and help you make significant progress in a shorter amount of time.